A Manual for the Design and Implementation of Teaching and Demonstration Gardens - Gail Hansen (EDIS)
Teaching and demonstration gardens are places where the public can learn about different types of gardens and landscapes. This 10-page fact sheet discusses the various types of gardens, how to plan and develop a demonstration garden, logistical and design considerations, and educational programming. Written by Gail Hansen, and published by the UF Environmental Horticulture Department, July 2015.